A 5-year retrospective study of demographic, anamnestic, and clinical factors related to psychiatric hospitalizations of adolescent patients - Di Lorenzo R (Dove Medical Press, 2016)
Rosaria Di Lorenzo,1 Nina Cimino,2 Elena Di Pietro,3 Gabriella Pollutri,4 Vittoria Neviani,5 Paola Ferri2 1Service of Psychiatric Diagnosis and Treatment, Department of Mental Health, AUSL Modena, Modena, 2School of Nursing, University of Modena and Reggio Emilia, 3School of Neuro-Psychiatry, 4School of Psychiatry, University of Modena and Reggio Emilia, 5 “The Medlar”, Villa Igea Hospital, Modena, Italy Background: Psychiatric emergencies of children and adolescents have greatly increased during the last years, but this phenomenon has not been studied in detail. The aim of this study was to analyze the correlation between acute psychiatric hospitalizations of adolescents and selected variables to highlight risk factors for psychiatric emergencies. Methods: This retrospective research was conducted in the acute psychiatric public ward, Service of Psychiatric Diagnosis and Treatment (SPDT), and in the residential facility for adolescents, “The Medlar”, located in Modena. The sample was constituted by all adolescent patients (n=101, age range 14–18) who had acute hospitalizations (n=140) in SPDT and had been successively transferred to “The Medlar” (n=83), from February 2, 2010 to January 31, 2015. From clinical charts, we extracted demographic and anamnestic characteristics of patients and clinical variables related to hospitalizations. Data were statistically analyzed. Results: Sixty-one percent of our patients lived with one divorced parent, with adoptive or immigrant family, or in institutions; 51% had experienced stressful events during childhood; 81% had a normal intellective level, but only 6% presented regular school performance. Parental psychiatric illness was negatively related, in a statistically significantly way, with onset age of adolescent mental disorders (coefficient -2.28, 95% confidence interval [CI]: -3.53 to 1.01, P<0.001, single linear regression; odds ratio: 4.39, 95% CI: 1.43–13.47, P<0.010, single logistic regression). The most frequent reasons for admission were aggressive behavior in males and suicide risk in females (P=0.002). The most frequent psychiatric diagnosis at SPDT discharge was “conduct disorder”, more frequent in males, followed by “adjustment disorder”, more frequent in females (P=0.001). In SPDT, the adolescent hospitalizations progressively increased fivefold at the end of the observation period. Conclusion: Our results overlap the worldwide trend of increasing adolescent psychiatric hospitalizations, suggest risk factors like parental psychiatric illness and early life stressful events, and highlight the different prevalence of aggressiveness and suicide in males and females. Keywords: psychiatric hospitalizations, adolescent patients, stressful events, mental disorders, suicide risk